Mt Owen Mine barrier pillar - Bartlett, WD; Clark, IH; McCormack, DE; Johnson, GD; Brown, AN (Slope Stability 2013: Proceedings of the 2013 International Symposium on Slope Stability in Open Pit Mining and Civil Engineering, 2013)
As the Mt Owen Mine progressed, turning from mining in a south westerly direction to a south easterly direction, in-pit dumping constraints demanded an innovative solution to prevent potential lowwall instabilities. An in situ rock pillar was designed to retain waste spoil, this was termed the ‘barrier pillar’. Measuring 270 m high and over a kilometre long, consisting of over 40 Mbcm of in situ rock and retaining in excess of 160 Mm3 of waste spoil. It is considered that the barrier pillar is the world’s largest in situ rock mass earth retaining structure. Stability of the barrier pillar was governed by the weak tuffaceous layers within the coal that have caused historical instabilities. Analyses of the barrier pillarhave been undertaken throughout the mine life; as the mine design evolved, so did the pillar design. The initial analysis was undertaken using a two-dimensional limit equilibrium model with multiple sections. Due to the complex nature of the geological structure, a subsequent analysis was undertaken using FLAC3D. Three pillar designs were analysed through thirteen stages of mining in order to predict rock mass behaviour through the proposed mining sequence, identify potential instability and determine the most appropriate pillar design. Automated prism monitoring and two brands of slope stability radars were used to monitor displacement of the barrier pillar. No significant displacement was detected during mining prompted an investigation into maximising coal recovery. Two-dimensional limit equilibrium analysis was used to assess the design. Comparisons were made between the successfully mined goodbye cut and the original FLAC3D modelled pillars to ensure no additional modelling was required.